Three-year assessment of cognitive and olfactory disturbances among COVID-19 convalescent patients grouped by olfactory hallucination status in Armenia: A qualitative and quantitative study - Karine Melkumyan; Syuzanna Simonyan; Darshan Shingala; Hrag Torossian; Karen Mkrtumyan; Milena Tulbenjyan; Yekaterina Hovhannisyan; Konstantin Yenkoyan (Clinical Medicine)
Background: Smell disturbances, memory and mood changes are frequently reported as symptoms of long COVID that can be debilitating and long-lasting, having a detrimental impact on a patient’s quality of life and possibly contributing to depression and a decline in cognitive abilities. Study objective: This study aims to investigate long-term post-COVID cognitive and olfactory disturbances among the COVID-19 convalescent adult Armenian population aged between 18 and 65 years. The assessment extends to the differentiation of various olfactory distortions and association between various olfactory and cognitive variables, grouped by participants’ olfactory hallucination status. Study design: Explanatory sequential mixed-methods design was employed. Through three follow-up visits, the quantitative phase evaluated olfactory and cognitive abnormalities following COVID-19, comparing those with and without olfactory hallucinations. Through in-depth interviews, the qualitative phase investigated how participants perceived these symptoms and their impact on their quality of life. Study participants: The quantitative study participants were those who self-reported subjective disturbances in the olfactory perception 14 days following a COVID-19 diagnosis, as confirmed by a positive PCR test at the time of diagnosis. The qualitative study participants were those who self-reported persistent olfactory disturbances post-visit 3. Results: The study found that olfactory hallucinations lead to more pronounced depression compared with non-hallucinogenic types of olfactory disturbances. It was determined that a significant predictor of parosmia is persistent anosmia up to 4 months following COVID-19 infection. Conclusion: The long-term olfactory disturbances post-COVID-19 infection have a better prognosis among participants without olfactory hallucination compared to participants with olfactory hallucination.